Economic and Social Survey of Asia and the Pacific 1996 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 1996)
Analyzes recent economic and social developments in the region with particular emphasis on economic and social policy issues and broad development strategies. This publication is invaluable to every multinational corporation intending to expand their business in Asia or to invest in the region.